The effect of directive tutor guidance in problem-based learning of statistics on students' perceptions and achievement - Budé, Luc; Imbos, Tjaart; v. d. Wiel, Margaretha W. J.; Broers, Nick J.; Berger, Martijn P. F. (Higher education, 2009)
In this study directive tutor guidance in problem-based learning (PBL) of statistics is investigated. In a quasi experiment in an educational setting, directive guiding tutors were compared with tutors in a more traditional role. Results showed that the subjective perceptions of the students with regard to the course, the tutor, and the discussions in the tutorial meetings were more positive in the guided condition. The quality of the problems used in the meetings and general tutor functioning were evaluated as equal in both conditions. Achievement was marginally higher in the guided condition. It can be concluded that directive tutor guidance is an effective addition to PBL of statistics.